PERAN BRAND IMAGE, KUALITAS PRODUK, DAN HARGA KOMPETITIF TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN ES KRIM AICE OLEH GEN-Z PONTIANAK - Nathania, Andrea; Graceallah, Georgerius (JURNAL DIMENSI, 2025)
The phenomenon that occurs is that AICE ice cream sales have decreased due to new players in the industry offering ice cream products with attractive characters. Brand image, product quality, and competitive price as independent variables while customer satisfaction as the dependent variable and purchasing decisions as intervening variables. Through the use of simple random sampling, this research adopts a quantitative approach and is based on primary data which is obtained from a questionnaire containing granular questions distributed to Gen-Z Pontianak. A total of 151 respondents were involved as samples in this study by utilizing data processing through IBM SPSS 26 to obtain results that can support the smooth running of this research. The findings of the study show that brand image and competitive price have a significant positive effect through purchasing decisions on customer satisfaction, product quality has a positive but insignificant effect through purchasing decisions on customer satisfaction and purchasing decisions as intervening contribute significantly to customer satisfaction.